CRAFTING THE FINANCIAL BLUEPRINT: STRATEGIES FOR ESTABLISHING AN ENTERPRISE'S ACCOUNTING FRAMEWORK - Atabayeva Zamira Abdujalilovna (Western European Studies, 2023)
This article delves into the intricacies of forming an accounting policy within an enterprise. It thoroughly explores the methodology, organization, and technical facets integral to an entity's accounting policy. The concept of "accounting policy" is extensively elucidated, delving into its content, significance, and fundamental essence. Detailed insights are offered into the primary elements constituting an accounting policy, alongside the organizational and technical principles governing their execution. Furthermore, the article navigates through the regulatory and legislative framework, highlighting the requisites essential in shaping an organization's accounting policy. It serves as a comprehensive guide, shedding light on the critical aspects involved in crafting and implementing an effective accounting policy within a business entity
Keywords: accounting policy; accounting methods; formation; tax